2014
DOI: 10.1002/cbic.201300687
|View full text |Cite|
|
Sign up to set email alerts
|

Hybrid Photopatterned Enzymatic Reaction (HyPER) for in Situ Cell Manipulation

Abstract: The ability to design artificial extracellular matrices as cell instructive scaffolds has opened the door to technologies capable of studying cell fate in vitro and to guide tissue repair in vivo. One main component of the design of artificial extracellular matrices is the incorporation of biochemical cues to guide cell phenotype and multicellular organization. The extracellular matrix is composed of a heterogeneous mixture of proteins that present a variety of spatially discrete signals to residing cell popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…The resultant μgel building blocks were composed of a completely synthetic hydrogel mesh of multi-armed poly(ethylene)glycol-vinyl sulfone (PEG-VS) backbones decorated with cell-adhesive peptide (RGD) and two previously utilized transglutaminase peptide substrates 2931 (K and Q). The μgels were crosslinked via Michael type addition with cysteine-terminated matrix metalloprotease-sensitive peptide sequences that allowed for cell-controlled material degradation and subsequent resorption.…”
Section: From Building Blocks To Porous Scaffolds: μGel Properties Dementioning
confidence: 99%
“…The resultant μgel building blocks were composed of a completely synthetic hydrogel mesh of multi-armed poly(ethylene)glycol-vinyl sulfone (PEG-VS) backbones decorated with cell-adhesive peptide (RGD) and two previously utilized transglutaminase peptide substrates 2931 (K and Q). The μgels were crosslinked via Michael type addition with cysteine-terminated matrix metalloprotease-sensitive peptide sequences that allowed for cell-controlled material degradation and subsequent resorption.…”
Section: From Building Blocks To Porous Scaffolds: μGel Properties Dementioning
confidence: 99%
“…This has been employed to immobilize peptides and proteins in three dimensional hydrogels. 77,78 In particular, cellular adhesion or directed 3D migration could be achieved by patterning a peptide (RGD), a fibronectin fragment, or a full length protein (platelet-derived growth factor) (Figure 14). 77 Such site specific-modifications may prove particularly useful for the immobilization of fragile biomolecules.…”
Section: Photocaging Reactionsmentioning
confidence: 99%
“…This method could ligated a myriad of proteins with the PEG network under mild conditions, which suggested that it could represent a powerful method to fabricate complex hydrogel matrices with spatiotemporal control over protein distribution [239]. A similar approach was reported by Griffin et al to prepare hydrogels with 3D protein patterns in the presence of cells [240]. …”
Section: Temporal Control Of Hydrogelmentioning
confidence: 99%